2020
DOI: 10.3390/app10134566
|View full text |Cite
|
Sign up to set email alerts
|

Automated Assessment and Microlearning Units as Predictors of At-Risk Students and Students’ Outcomes in the Introductory Programming Courses

Abstract: The number of students who decided to study information technology related study programs is continually increasing. Introductory programming courses represent the most crucial milestone in information technology education and often reflect students’ ability to think abstractly and systematically, solve problems, and design their solutions. Even though many students who attend universities have already completed some introductory courses of programming, there is still a large group of students with lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 34 publications
0
14
0
6
Order By: Relevance
“…One of the hottest research topics in learning analytics has been predicting the probability of students completing or failing a course, especially from the very early weeks [13], as well as EDM [14]. Once a reliable performance prediction is available, it can be used in many contexts to identify weak students and provide feedback to students or predict students' failure [15].…”
Section: Related Workmentioning
confidence: 99%
“…One of the hottest research topics in learning analytics has been predicting the probability of students completing or failing a course, especially from the very early weeks [13], as well as EDM [14]. Once a reliable performance prediction is available, it can be used in many contexts to identify weak students and provide feedback to students or predict students' failure [15].…”
Section: Related Workmentioning
confidence: 99%
“…Skalka & Drlik [47] concluded that AA does not degrade students' results, but its significant improvement in them was not proved. More detailed research by the same researchers [4] has shown that the use of AA in the introductory lessons of programming courses led to significant student outcomes differences. The initial topics, such as input/output, variables, data types, nested loops, arrays, exceptions, files, etc., cover essential issues.…”
Section: Automated Assessmentmentioning
confidence: 99%
“…The H1 hypothesis requires a comparison of students' results measured by two tests. The tests were focused on the practical experience of students and consisted of several (3)(4)(5) assignments that covered the entire content of the first or second half of the course content.…”
Section: Post-testmentioning
confidence: 99%
See 2 more Smart Citations